Genotyping of Toxoplasma gondii in wild boar (Sus scrofa) in southern Italy: Epidemiological survey and associated risk for consumers. (4th September 2020) - Sgroi, Giovanni; Viscardi, Maurizio; Santoro, Mario; Borriello, Giorgia; D'Alessio, Nicola; Boccia, Federica; Pacifico, Laura; Fioretti, Alessandro; Veneziano, Vincenzo; Fusco, Giovanna
Abstract: Toxoplasma gondii is a widespread protozoan parasite (phylum Apicomplexa), which causes a zoonotic parasitic disease, known as toxoplasmosis. The aim of this study was to evaluate the occurrence and genotypes of T. gondii in wild boars of southern Italy and thus to assess the risk of infection for consumers. The boars were inspected during the hunting season within the regional project ' Wild Boar Emergency Plan in Campania ', and molecular analyses were performed on 338 boars analysing a total number of 884 matrices (263 brains, 310 hearts and 311 masseter muscles). Toxoplasma gondii was detected in 134 out of 338 boars (39.6%). No significant statistical difference between genders was found (χ 2 = 0.15 p = .70). The prevalence was 47.1%, 39.3% and 39.2% in piglets, yearlings and adults, respectively (χ 2 = 0.41; p = .81). The highest prevalence of T. gondii was found in masseter muscles (74/311, 23.8%), followed by the heart (70/310, 22.6%) and brain (58/263, 22.0%), respectively. Microsatellite (MS) analysis of 11 samples revealed eleven T. gondii genotypes (nine atypical, one belonging to type II one to type III). Most of the genotypes found were thus atypical and may be virulent in humans. Hierarchical clustering analysis showed the presence of three distinct clusters, with the majority of atypical genotypes in the GII‐GIII cluster. The high prevalence of infection in masseters highlights the potential risk for public health, considering that this muscle is commonly used to prepare raw meat products ('guanciale' and sausages), which may be a source of T. gondii infection in humans. Wild boars may act as an interface role between wildlife, livestock and humans. Our data highlight the urgent need to minimize the risk of infection for animals and humans by setting up a surveillance programme and preventive strategies in a One Health approach to wildlife species.